Opposing retrograde and astrocyte-dependent endocannabinoid signaling mechanisms regulate lateral habenula synaptic transmission - Nathan D. Winters; Veronika Kondev; Niharika Loomba; Eric Delpire; Brad A. Grueter; Sachin Patel (Cell Reports, 2023)
Summary: The lateral habenula (LHb) encodes aversive states, and its dysregulation is implicated in neuropsychiatric disorders, including depression. The endocannabinoid (eCB) system is a neuromodulatory signaling system that broadly serves to counteract the adverse effects of stress; however, CB1 receptor signaling within the LHb can paradoxically promote anxiogenic- and depressive-like effects. Current reports of synaptic actions of eCBs in the LHb are conflicting and lack systematic investigation of eCB regulation of excitatory and inhibitory transmission. Here, we report that eCBs differentially regulate glutamatergic and GABAergic transmission in the LHb, exhibiting canonical and circuit-specific inhibition of both systems and an opposing potentiation of synaptic glutamate release mediated via activation of CB1 receptors on astrocytes. Moreover, simultaneous depression of GABA and potentiation of glutamate release increases the net excitation-inhibition ratio onto LHb neurons, suggesting a potential cellular mechanism by which cannabinoids may promote LHb activity and subsequent anxious- and depressive-like aversive states.